Urban Reality of Type 2 Diabetes among First Nations of Eastern Ontario: Western Science and Indigenous Perceptions - Ghosh, Hasu (The Centre for Global Citizenship Education & Inclusion, 2012)
This paper presents an anthropological investigation of perception and management of Type 2 Diabetes among First Nations people in an Eastern Ontario urban setting. Applying the concept of structural violence and based on the semi-structured interviews conducted with urban First Nations people and health care professionals, findings of this study reflect that diabetes is entangled in a complex web of social and cultural circumstances that make the coping and management of this disease very challenging for today's First Nations people. Results also document the shared social, cultural and historical circumstances which have contributed to the emergence of diabetes among First Nations people. Diabetes in this regard can be viewed as a reflection of economic and social conditions, but also low self-esteem and self-worth arising from a colonial past. These perspectives have repercussions for reaction to diabetes diagnosis and coping strategies around diet, physical activity and medication. Existing levels of diabetes management strategies, including treatment, support and education meet the urban First Nation peoples' need to some extent. The paper concludes with the recommendations for development of future health and social programmes that engage stakeholders and pay considerable attention to their strengths and needs.